CivilWarLand in bad decline : stories and a novella - Saunders, George, 1958- (Riverhead Books, 1997)
A novella and short stories on a future America, a land of corporate hypocrisy, violence and pollution. Trendy attractions include pickled babies and cows with plexiglass sides, so you can see the milk made, people buy other people's more interesting memories for downloading into their heads.